Geometric progression 4
Leave us a comment of example and its solution (i.e. if it is still somewhat unclear...):
Showing 0 comments:
Be the first to comment!
To solve this example are needed these knowledge from mathematics:
Next similar examples:
- Geometric progression
Fill 4 numbers between 4 and -12500 to form geometric progression.
The computer was purchased 10000,-. Each year, the price of a computer depreciates always the same percentage of the previous year. After four years, the value of the computer is reduced to 1300,- How many percent was depreciated price of the computer each
- Geometric sequence 4
It is given geometric sequence a3 = 7 and a12 = 3. Calculate s23 (= sum of the first 23 members of the sequence).
- GP - 8 items
Determine the first eight members of a geometric progression if a9=512, q=2
- Five members
Write first 5 members geometric sequence and determine whether it is increasing or decreasing: a1 = 3 q = -2
- Tenth member
Calculate the tenth member of geometric sequence when given: a1=1/2 and q=2
- Six terms
Find the first six terms of the sequence a1 = -3, an = 2 * an-1
- Geometric progression 2
There is geometric sequence with a1=5.7 and quotient q=-2.5. Calculate a17.
- GP members
The geometric sequence has 10 members. The last two members are 2 and -1. Which member is -1/16?
Find the common ratio of the sequence -3, -1.5, -0.75, -0.375, -0.1875. Ratio write as decimal number rounded to tenth.
- A perineum
A perineum string is 10% shorter than its original string. The first string is 24, what is the 9th string or term?
- Geometric sequence 5
About members of geometric sequence we know: ? ? Calculate a1 (first member) and q (common ratio or q-coefficient)
- Sequence 3
Write the first 5 members of an arithmetic sequence: a4=-35, a11=-105.
How much is sum of square root of six and the square root of 225?
Number ?. Find the value of x.
- Quadratic equation
Find the roots of the quadratic equation: 3x2-4x + (-4) = 0.
- Theorem prove
We want to prove the sentense: If the natural number n is divisible by six, then n is divisible by three. From what assumption we started?